Status of female teachers in the Middle East and North Africa Region - Ayyash-Abdo, Huda (2006)
The purpose of this study was to examine the status of female teachers in nine Middle Eastern and North African countries. The results indicated that ineffective pre-service and in-service training, teachers' educational level, and lack of follow up of female teachers at all levels has limited professional competency and growth. In addition, socio-cultural constraints on women have made a negative impact and have contributed to the existing gender disparity. It was also found that lack of monetary and non-monetary incentives negatively impacted the status of female teachers. In light of this assessment, implications are drawn to dramatically increase the time committed to in-service and pre-service training as well as mentor programs. In addition, distance education could also be a viable strategy for training teachers in the region.